Lower Four Cranial Nerves in the Management of Glomus Jugulare: Anatomical Study - Fayed, Ashraf; El-Deeb, Mohamed E.; Magnan, Jacques; Meller, Renaud; Deveze, Arnaud; Elzayat, Saad (International Archives of Otorhinolaryngology, 2023)
Introduction The surgical management that achieves minimal morbidity and mortality for patients with glomus and non-glomus tumors involving the jugular foramen (JF) region requires a comprehensive understanding of the complex anatomy, anatomic variability, and pathological anatomy of this region.Objective The aim of this study is to propose a rational guideline to expose and preserve the lower cranial nerves (CNs) in the lateral approach of the JF.Methods The technique utilized is the gross and microdissection of 4 fixed cadaveric heads to revise the JF's surgical anatomy and high part of the carotid sheath compared with surgical cases to understand and preserve the integrity of lower CNs. The method involves radical mastoidectomy, microdissection of the JF, facial nerve, and high neck just below the carotid canal and the JF. The CNs IX, X, XI, and XII are microscopically dissected and kept in sight up to the JF.Results This study realized well the surgical and applied anatomy of the lower CNs with relation to the facial nerve and JF.Conclusions The JF anatomy is complicated, and the key to safely operate on it and preserving the lower CNs is to find the posterior belly of the digastric muscle, to skeletonize the facial nerve, to remove the mastoid tip preserving the stylomastoid foramen, to skeletonize the sigmoid sinus and posterior fossa dura not only anterior but also posteroinferior to reach and drill the jugular tubercle.
Keywords: cadaveric study; facial nerve; jugular foramen; lower cranial nerves; surgical anatomy